Flow Electrification Investigation Under the Effect of the Flow Parameters - Leblanc, Paul (2018)
When a liquid is in contact with a solid, a physicochemical reaction occurs at the solid-liquid interface leading to the formation of the electric double layer. Whenever the mobile portion of this charge inside the liquid is swept by the flow, a chemical reaction occurs and leads to the flow electrification process. According to the classical theory of this phenomenon, it is assumed that the laminar flow has no impact on the physicochemical behavior at the interface. However, recent studies have shown that this supposition is not consistent with the experimental results. The aim of this work is to highlight the impact of the flow parameters on the flow electrification phenomenon in the case of mineral oil flows through a stainless steel capillary. In this purpose, the capillary is shortened to keep the same contact duration between the solid and the liquid at different mean flow velocities.